STUDI ANALISIS KEKERASAN SEKSUAL PADA REMAJA DI KABUPATEN GUNUNGKIDUL - Tutik Astuti; Vio Nita (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
Adolescent Sexual Violence Analysis Study In Gunungkidul RegencyBackground : Cases of sexual violence against women in DIY need to get serious restraint. The courage of reporting from victims is necessary to break the chain of sexual crimes. Rifka Annisa accompanied 29 cases of child sexual abuse in 2017, the majority of which were women.. The vulnerable cases of sexual violence color Gunungkidul Regency throughout the beginning of 2019. Based on data from DP3AKBPMD (Office of Child Empowerment Family Planning Community and Village Empowerment), a total of 24 cases were reported in 2018, with details of 9 cases of violence against women and 15 cases of child abuse, as well as 5 cases of child sexual. Objective : To know the factors behind the occurrence of sexual violence in adolescence in Gunungkidul regency. Methods : used is qualitative research that explains the main cause of adolescent violence. This research place is located in Gunungkidul Regency, Special Region of Yogyakarta, and data collection is conducted with in-depth interview techniques, the implementation of data collection in August - October 2020. Qualitative data processing is done by transcription, koding and necessary in narrative form. Results : the results showed that there are deep psychological problems in victims of violence with marked anxiety and concerns faced if sexual violence arises again. There is even a deep disappointment in the victim of sexual violence committed by her biological father. But victims of sexual violence experience helplessness accompanied by the ease with which the victim is offended when having to re-express the events experienced, even to the point of distrust of those around her who create an overwhelming fear of the victim. Conclusion : In cases of sexual violence in adolescents this causes psychological trauma to the victim, so it is necessary to assist the service provider and increase awareness of family and community.